Poly[di-μ(3)-chlorido-[μ(2)-(3-pyridyl)(4-pyridyl)methanone-κ(2) N:N′]dicopper(I)] - Hittle, Jennifer L. (International Union of Crystallography, 2008)
In the title compound, [Cu(2)Cl(2)(C(11)H(8)N(2)O)](n), stair-like ribbons of formula [Cu(2)Cl(2)](n) are linked into coordination polymer layers by tethering (3-pyridyl)(4-pyridyl)methanone (3,4′-dpk) ligands. The two distinct Cu(I) centres both adopt distorted CuNCl(3) tetrahedral coordinations. Individual [Cu(2)Cl(2)(3,4′-dpk)](n) layers stack in an AB pattern along the c direction by way of weak C—H⋯O interactions between the pyridyl rings and ketone O atoms.